Modeling and analysis of employee performance management based on system dynamics approach - Ulutaş, Samet. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Since human capital is gaining importance as a key driver of competitive advantage, there is an increasing interest for the value of Human Resources (HR). Thus, decision makers in the HR field need to focus on the critical issue of how to improve employee performance. The aim of this study is to explore and compare the performance of different employee performance management policiesby using System Dynamics (SD) simulation approach. Initially, the influential factors affecting employee performance are identified by using a Structural Equation Model (SEM), based on the data obtained from an Information Technology (IT) company. These factors are used as inputs in a SD model together with other variables, such as productivity andcost. The SD model is used to analyze the effects of using different performance evaluation policies on the realized performance scores of the employees, their overall productivity, their motivation level, overtime usage, employee turnover rate and HR related costs.With this motivation, the current performance evaluation system of the IT Company –which totally ignores the productivity levels of the employees– is modeled in a SD environment and its validity is checked by using structural and behavioral validity tests. Next, two new performance evaluation policies are provided to improve the poor performance of the current system. In the first policy, performance scores are created according to solely measured productivity of the employees; and in the second policy, performance scores are created according to partial productivity of the employees. The effect of the performance evaluation policies on the realized performances of the system are analyzed and compared under four scenarios generated by considering possible external events or introducing new variable relationships to the models.
Keywords: Employees -- Ratings of.; Performance management.